Targeting DNA Methyltranferases in Urological Tumors - Marques-Magalhães, Ângela; Graça, Inês; Henrique, Rui; Jerónimo, Carmen (Frontiers in Pharmacology, 2018)
Urological cancers are a heterogeneous group of malignancies accounting for a considerable proportion of cancer-related morbidity and mortality worldwide. Aberrant epigenetic traits, especially altered DNA methylation patterns constitute a hallmark of these tumors. Nonetheless, these alterations are reversible, and several efforts have been carried out to design and test several epigenetic compounds that might reprogram tumor cell phenotype back to a normal state. Indeed, several DNMT inhibitors are currently under evaluation for therapeutic efficacy in clinical trials. This review highlights the critical role of DNA methylation in urological cancers and summarizes the available data on pre-clinical assays and clinical trials with DNMT inhibitors in bladder, kidney, prostate and testicular germ cell cancers.